Ekonomska presoja enakih in usklajenih ravnanj na oligopolnih trgih - Ferčič, Aleš (LeXonomica, 2021)
Economic appraisal of equal- and concerted practices in oligopoly markets. In this article the author deals with certain aspects of the economic appraisal of equal- and concerted practices on oligopoly markets. These markets are – as regards to the institutional protection of market competition – the most problematic, since it is difficult to define clear limits between non-coordinated and coordinated equal market behaviour of undertakings. Here one can use various economic models. For this reason the author analyses certain economic models for appraisal of supposed concerted practices on oligopoly markets, giving their evaluation or assessment. In this regard the author ascertains that, in principle, (analysed) economic models are convenient instrument for delimitation between “natural” equal behaviours and concerted practices of undertakings. However, he also underlines their limits, as these models are mostly based on the presumption of stability or equilibrium, what is – within the market – an exception rather than a market rule. Povzetek. V tem prispevku avtor obravnava vidike ekonomske presoje enakih in usklajenih ravnanj podjetij na oligopolnih trgih, ki so z vidika kontrole oz. institucionalnega varstva tržne konkurence najbolj problematični, saj je zaradi tržnih zakonitosti težko razmejiti enaka ravnanja podjetij, tj. zaradi njihovega medsebojnega usklajevanja ali koordinacije. Pri tej presoji si lahko pomagamo z nekaterimi ekonomskimi modeli. Glede na to avtor v tem prispevku analizira nekatere ekonomske modele za presojo domnevnih usklajenih ravnanj na oligopolnih trgih in jih kritično ovrednoti. Na tej podlagi ugotavlja, da so dobrodošel pripomoček pri razumevanju naravnih enakih ravnanj in usklajenih ravnanj v smislu konkurenčnega prava, vendar ob tem opozarja na njihov omejen domet, ki izvira zlasti iz okoliščine, da analizirani modeli večinoma temeljijo na predpostavki stabilnosti oz. ravnovesij, ki pa so v praksi prej izjema kot pravilo.